Out-of-plane magnetized cone-shaped magnetic nanoshells. (17th February 2017) - Ball, D K; Günther, S; Fritzsche, M; Lenz, K; Varvaro, G; Laureti, S; Makarov, D; Mücklich, A; Facsko, S; Albrecht, M; Fassbender, J
Abstract: The geometry of a magnetic nano-object, namely its shape and dimensions determines the complex electromagnetic responses. Here, we address the geometry-induced changes of the magnetic properties of thin ferromagnetic Co/Pd multilayers with out-of-plane magnetic anisotropy deposited on three-dimensionally curved templates. For this purpose, arrays of self-assembled cone-shaped nano-objects with a chracteristic size of either 30 or 70 nm were created in GaSb(0 0 1) by the ion erosion technique. The templates are designed in the way that the shape of the cone remains the same for all the samples; namely, we keep the opening angle at about 55° by adjusting the ratio between the cone height and its base diameter to be about 1. In this case, we are able to address the impact of the linear dimensions of the object on the magnetic properties and exclude the impact of the shape from the consideration. The deposition of 15 nm thick Co/Pd multilayers on top of the cone templates results in the formation of a close-packed array of 2D magnetic cone-shaped shells. Integral angle-dependent magnetometry measurements demonstrate that the local curvature results in the spread of the easy axes of magnetization following the shape of the nanocones independent of the linear dimensions of the cones. At the same time different local magnetic domain patterns are observed for samples prepared on 30 and 70 nm large cones. When the thickness of the magnetic shell is only half of the linear dimension of a cone, a clear multidomain state is observed. Remarkably, we find that the neighboring magnetic cone-shaped shells are exchange decoupled when the linear dimension of a cone is four times larger compared to the thickness of the magnetic shell. These findings are relevant for the further development of tilted bit patterned magnetic recording media as well as for the emergent field of magnetism in curved geometries.